Lyotard's postmodernism and christianity: An investigation on christianity as a metanarrative and the possibility of its persistence in the age of postmodernity - Aguinaldo, Ryan Adrian M. (Animo Repository, 2021)
Lyotard describes postmodernism (or the postmodern condition) as incredulity towards metanarrative. On some occasions, he enlisted Christianity as a metanarrative. This research intends to make a survey of the responses of Christian scholars who defended Christianity from the postmodern critique by arguing that Christianity is not a metanarrative in Lyotard's sense. Given the three defining features of metanarrative provided by Justin Thacker, namely, second-level, legitimating and universal this research also presents an evaluation of the arguments of these counter-Lyotardian Christian scholars, namely, Smith, Westphal and Webster. In order to make a comprehensive survey, this research also includes the arguments of those Christian scholars who defended Christianity from the postmodern critique on the basis of its viability in the age of postmodernity. Middleton and Walsh respond to it through the two counter-ideological/anti-totalizing aspects of Christianity which proves that it does not succumb to violence unlike other modern grand narratives. However, to establish the possibility of persistence of Christianity in the age of postmodernity, the research takes on the philosophy of Lieven Boeve particularly on his notion of "recontextualization" and "Christian open narrative." Unlike the counter-Lyotardian Christian scholars who defended Christianity from the postmodern critique by focusing on one feature of metanarrative or by adding another feature to advance their agenda, Boeve, however, accepts the postmodern critique and analyzes Christianity on the characteristics which it shared with other modern grand narratives. The researcher recognizes that Boeve has advanced his arguments where Smith and Westphal failed to develop. This makes Lieven Boeve's reception of Lyotard's philosophy the most formidable response to postmodern critique.